Rational engineering of Escherichia coli strain for stable and enhanced biosynthesis of pinene - Hussain, Muhammad Hammad; Han, Lu; Wei, Yanlong; Javid, Muhammad; Ashraf, Kamran; Martuscelli, Maria; Aldahmash, Waleed; Guo, Meijin; Mohsin, Ali; Li, Zhanxia (Frontiers in Microbiology, 2025)
Monoterpene α-pinene exhibits significant potential as an alternative fuel, widely recognized for its affordability and eco-friendly nature. It demonstrates multiple biological activities and has a wide range of applications. However, the limited supply of pinene extracted from plants poses a challenge in meeting the needs of the aviation industry and other sectors. Considering this, the microbial cell factory is the only viable option for achieving sustainable pinene production. This study employed a rational design model to optimize the copy number and integration site for the heterogenous pinene expression pathway in Escherichia coli (E. coli). The integrated strain with the best pinene pathway PG1 was selected. Subsequently, the resulting strain, E. coli HSY009, accumulated 49.01 mg/L of pinene after 24 h fermentation in the flask culture. To further enhance production, pinene expression cassette PG1 was sequentially integrated into three non-essential regions (44th, 58th, 23rd), resulting in an improved pinene titer. Then, the fermentation process under optimized conditions enhanced the production of pinene to 436.68 mg/L in a 5 L batch fermenter with a mean productivity of 14.55 mg/L/h. To the best of our knowledge, this work represents the maximum mean pinene productivity based on the currently available literature. The findings of this work provide valuable insights for optimizing E. coli to produce other valuable terpenoids that share the same intermediates, IPP and DMAPP. Conclusively, this research validates the model’s universality and highlights its potential for application as cutting-edge biofuel precursors.